한국 재래종 벼 유묘기 뿌리 발달 전장유전체연관분석 - 서정환(Jeonghwan Seo); 장홍지아(Hongjia Zhang); 이아림(Ah-Rim Lee); 이원도(Wondo Lee); 조유현(Yoo-Hyun Cho); 권순욱(Soon-Wook Kwon); 이주현(Joohyun Lee) (Korean journal of breeding, 2021)
Root development at the seedling stage is an important trait for the early growth of rice. In this study, the root length and weightof 211 Korean landrace rice at the seedling stage were evaluated, and the average root length and weight were 6.94 cm and 48.18 mg, respectively. Principal component analysis (PCA) of 211 accessions based on 70,849 SNPs presented three subgroups. Two quantitative trait loci (QTLs)associated with root length were detected on chromosomes 3 and 6 using genome-wide association study (GWAS). Four haplotypes wereidentified using associated SNPs for the two root length QTLs. The average root length of Hap2 and Hap 3 was 7.32 cm and 6.56 cm,respectively, and were significantly different. Gene expression analysis in the candidate regions of QTLs for root length at the seedling stageshowed that several genes were expressed in the root. QTLs associated with root length at the seedling stage identified in this study maybe applied to improve the root length trait and detect candidate genes. KCI Citation Count: 0